Studying the short-run dynamics of inflation: Estimating a hybrid new-keynesian Phillips Curve for Argentina (1993-2007) - Laura D'Amato; María Lorena Garegnani (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2009)
We estimate a 'Hybrid New-Keynesian Phillips Curve' for Argentina between 1993 and 2007. We extend the model to a small open economy, considering separately the influence of nominal devaluation and foreign inflation on domestic prices. For the whole sample, we find that forward and backward-looking components are relevant although the backward-looking term weights more in determining inflation dynamics. We test for parameter stability and find a break-point in 2002 along with the regime change. In line with recent literature on trend inflation, when trend inflation increases, the influence of the output gap weakens and the curve becomes more forward-looking.
Keywords: C5; E31; 330; Argentina; inflation dynamics; Phillips Curve; small open economy; New-Keynesian Phillips Curve; Argentinien